Nilai Ekoteologi dalam Qur’an dan Hadis serta Implementasinya dalam Pembelajaran Pendidikan Agama Islam Berbasis Projek - Rosyida Nurul Anwar; Muhammad Faizul Husnayain (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Environmental damage does not only originate from industrial technical factors, but also from human mindsets and value orientations. Ecotheology is a concept that discusses the interrelationship between theological-philosophical views in religious teachings with nature, especially the environment. The purpose of this study is to analyze the ecotheological values in the Qur'an and Hadith in project-based Islamic Religious Education. The research method uses a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawing using the Miles & Huberman model. The research participants were 58 students enrolled in an Islamic Religious Education learning project on ecotheology. The results of this study indicate that the integration of ecotheological values in project-based learning is able to foster students' ecological awareness in three main dimensions: (1) theological-emotional understanding of the human mandate as guardians of the earth, (2) ecological attitudes reflected in increased concern and sensitivity to environmental issues, and (3) ecological praxis in the form of active student involvement in environmental conservation actions. Project-based Islamic Education creates reflective, applicable, and meaningful learning experiences by connecting sacred texts to ecological realities.